Change of weight status during school age and its association with late adolescent blood pressure: Results from a 15-year longitudinal study in China - Wang, Xijie; Dong, Yanhui; Huang, Sizhe; Dong, Bin; Ma, Jun; Liang, Wannian (Frontiers in Public Health, 2022)
Background Change in obesity risk could be related to shift in high blood pressure (HBP) risk, while individualized influence of weight change on high blood pressure is in need of exploration. Methods A total of 16,446 children (53.47% boys) and 13,9021 effective annual measurements from 2006 to 2020 were recruited. Children's weight status, both at baseline and endpoint, was categorized as underweight, normal, overweight, and obese according to the age and sex-specific Body Mass Index z scores. HBP at late adolescence was defined with the last two measurements for each child. Populational attributable risk (PAR) of weight trait on HBP risk was calculated. Results Compared to children who maintained normal weight during follow-up, staying obese was associated with the highest HBP risk with OR of 6.39 (95% CI: 4.46, 9.15; p < 0.001) and PAR of 28.71% (95% CI: 21.58, 35.54) in boys, and OR of 6.12 (95% CI: 2.80, 13.37; p < 0.001) and PAR of 12.75% (95% CI: 4.29, 21.02) in girls. Returning from obese to normal weight was associated with lowered HBP risk, with ORs of 1.07 (95% CI: 0.69, 1.66; p = 0.771) in boys and 0.73 (95% CI: 0.25, 2.12; p = 0.566) in girls. Conclusion Weight loss program could be effective to reduce HBP risk during school age, while the underlying mechanism needs further exploration.